Comprehensive genetic dissection of the hemocyte immune response in the malaria mosquito Anopheles gambiae. - Fabrizio Lombardo (Public Library of Science (PLoS), 2013)
Reverse genetics in the mosquito Anopheles gambiae by RNAi mediated gene silencing has led in recent years to an advanced understanding of the mosquito immune response against infections with bacteria and malaria parasites. We developed RNAi screens in An. gambiae hemocyte-like cells using a library of double-stranded RNAs targeting 109 genes expressed highly or specifically in mosquito hemocytes to identify novel regulators of the hemocyte immune response. Assays included phagocytosis of bacterial bioparticles, expression of the antimicrobial peptide CEC1, and basal and induced expression of the mosquito complement factor LRIM1. A cell viability screen was also carried out to assess dsRNA cytotoxicity and to identify genes involved in cell growth and survival. Our results identify 22 novel immune regulators, including proteins putatively involved in phagosome assembly and maturation (Ca²⁺ channel, v-ATPase and cyclin-dependent protein kinase), pattern recognition (fibrinogen-domain lectins and Nimrod), immune modulation (peptidase and serine protease homolog), immune signaling (Eiger and LPS-induced factor), cell adhesion and communication (Laminin B1 and Ninjurin) and immune homeostasis (Lipophorin receptor). The development of robust functional cell-based assays paves the way for genome-wide functional screens to study the mosquito immune response to infections with human pathogens.